Immunomodulatory Agents for Multiple Myeloma - Minařík, Jiří; Ševčíková, Sabina (Cancers, 2022)
The treatment of multiple myeloma (MM) has undergone a significant paradigm shift in the last 20 years, from conventional chemotherapy to more tumor-specific treatments, based on the interference with pathogenesis of the malignant clone as well as the bone microenvironment [...].